Interactive Learning Media in Fifth-Grade Indonesian Elementary School Subjects - Ismawati; Desak Putu Parmiti; I Gde Wawan Sudatha (International Journal of Elementary Education, 2023)
Instructional media have yet to be applied innovatively and variedly in the delivery of Indonesian language material so that it impacts the learning outcomes of fifth-grade elementary school students. This study analyzes interactive learning media's development process, validity, and effectiveness on learning outcomes in Indonesian subjects. This research is included in research development (Research & Development). The test subjects in this study were one material expert, one media expert, one design expert, and 24 fifth-grade elementary school students. Data collection methods used are questionnaires and tests. This study used three data analysis techniques: qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical techniques (t-test). The results of this study indicate that the validity results obtained by material experts are 96.36% (very good), design experts are 95% (very good), media experts are 94.66% (very good), and responses from students are confident in individual trials 85 .08% (good), small group trials 83.47% (good), and field trials 80.20% (good). Based on the pre-test results of 61.67 percent (poor) and the post-test results of 85.25 percent (good). The results show that the significance level is less than 0.05. (p˃0.05). Based on the results of this analysis, it can be concluded that interactive learning media is valid and effective in improving the learning outcomes of fifth-grade elementary school students.